Relationship of sleep and perceived effort in collegiate women basketball athletes - Cammarano, G.; Fields, J.; Wong, D.; Brown, F.; Baker, R.; Jones, M. (The Journal of Strength and Conditioning Research, 2021)
Attainment of ideal sleep quantity and quality can be difficult for collegiate athletes due to the heightened demands of sport and academic schedules. Both sleep quantity and quality have been shown to inversely impact pre-training fatigue levels and post-training athlete perceived effort. Reduced sleep has been associated with decreased performance and a heightened risk of injury. However, no data exist for collegiate women athletes in regard to sleep quantity and quality and their impact upon athlete ratings of perceived exertion of exercise sessions. Purpose: To investigate the relationship between sleep quantity and quality and perceived exertion during pre-season training and in-season practices and games for collegiate women basketball athletes. Methods: National Collegiate Athletic Association Division I women basketball athletes (n = 14, mean ± SD age: 20 ± 1.53 years; body mass: 81.23 ± 18.7 kg; height: 177.08 ± 8.36 cm; body fat: 23.17 ± 7.66%) participated. Data were collected over a 3-month period that consisted of pre-season training (30 practices) and non-conference game play (30 practices, 13 games). Each day, immediately upon waking, athletes used their mobile phones to complete self-reported measures via an electronic questionnaire. The self-reported measures employed a Likert scale from 1 to 5 for sleep quality, and sleep quantity was reported as number of hours slept. Five minutes after each exercise session (i.e., practices, games), athletes reported their Rating of Perceived Exertion (RPE) using the Borg CR-10 Scale. The session's RPE was then calculated (RPE × training duration in minutes). One-way analysis of variance was utilized to assess differences in sleep quality and quantity during the pre-season and in-season (p < 0.05). In addition, multiple regression analyses assessed: 1) the relationship between sleep quality and quantity with sRPE for the pre-season and in-season periods and 2) the relationships between sleep quality and quantity with sRPE for games. Results: Sleep quality (p < 0.001) and quantity (p < 0.001) were lower in the pre-season (3.6 and 6.7 hours, respectively) compared to in-season (3.7 and 7.2 hours, respectively). Sleep quality and quantity were not associated with post-game or post-practice sRPE values during pre-season or in-season periods. Conclusion: Athletes reported improved sleep quality and quantity during in-season compared to pre-season. However, there was no relationship between sleep and sRPE. It is recommended that future research examine sleep and its association with other wellness self-reported measures as well as performance assessments. Practical Application: Improved sleep during high periods of competition is beneficial for achieving optimal performance, reducing risk of injury, and maintaining overall health. Since there was no relationship between sleep quality and quantity and sRPE, athletes may not perceive sleep to have an adverse impact on their game performance. Although sRPE has shown to be a strong indicator of training load, sleep perception may not play a role.